Analisis Kesantunan Berbahasa Mahasiswa pada Mata Kuliah Bahasa Indonesia di STITNU Al Mahsuni - Baiq Desy Arfini (Jurnal Ilmiah Telaah, 2023)
This type of research is descriptive qualitative using the case study method which aims to describe the form, principles, and level of language politeness among STITNU AL Mahsuni students. The results of this study show that among female students when conducting discussions, there are still those who use language that is not polite. But in the results of the study, observations and data analysis of the level of language politeness in the category are quite polite. From the results of the study, it can be concluded that the form of language politeness when discussing in class has been included in the polite category even though some still use less polite language. This indicates that in principle students in speaking words either act as speakers or become speech speech that still violates the maxim of politeness